Peripheral Blood Mitochondrial DNA Levels Were Modulated by SARS-CoV-2 Infection Severity and Its Lessening Was Associated With Mortality Among Hospitalized Patients With COVID-19 - Valdés-Aguayo, José J.; Garza-Veloz, Idalia; Vargas-Rodríguez, José R.; Martinez-Vazquez, María C.; Avila-Carrasco, Lorena; Bernal-Silva, Sofia; González-Fuentes, Carolina; Comas-García, Andreu; Alvarado-Hernández, Diana E.; Centeno-Ramirez, Alba S. H.; Rodriguez-Sánchez, Iram P.; Delgado-Enciso, Ivan; et al. (Frontiers in Cellular and Infection Microbiology, 2021)
Introduction. During severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection, the virus hijacks the mitochondria causing damage of its membrane and release of mt-DNA into the circulation which can trigger innate immunity and generate an inflammatory state. In this study, we explored the importance of peripheral blood mt-DNA as an early predictor of evolution in patients with COVID-19 and to evaluate the association between the concentration of mt-DNA and the severity of the disease and the patient’s outcome. Methods. A total 102 patients (51 COVID-19 cases and 51 controls) were included in the study. mt-DNA obtained from peripheral blood was quantified by qRT-PCR using the NADH mitochondrial gene. Results. There were differences in peripheral blood mt-DNA between patients with COVID-19 (4.25 ng/ul ± 0.30) and controls (3.3 ng/ul ± 0.16) (p = 0.007). Lower mt-DNA concentrations were observed in patients with severe COVID-19 when compared with mild (p= 0.005) and moderate (p= 0.011) cases of COVID-19. In comparison with patients with severe COVID-19 who survived (3.74 ± 0.26 ng/ul) decreased levels of mt-DNA in patients with severe COVID-19 who died (2.4 ± 0.65 ng/ul) were also observed (p = 0.037). Conclusion. High levels of mt-DNA were associated with COVID-19 and its decrease could be used as a potential biomarker to establish a prognosis of severity and mortality of patients with COVID-19.